(untitled) (Fiep Bulletin - online, 2015)
The guiding factors that have led this work are connected and subsequent, they are: people who have suffered an accident and had their spinal cord injured, specifically the cervical part, advances in medicine, motor rehabilitation and the possible roles of a Physical Education on the process of neuroplasticity. This study aims to describe the insertion of physical education professional in the process of neuroplasticity of an individual who suffers from a cervical cord injury. For this purpose the research is of the descriptive type characterized as a study case. The subjects are three professionals, among them two physiotherapists and a Physical Education professional, who were enquired with questions related to the neuroplasticity process. The result of the study showed that the insertion of a physical education professional in the neuroplasticity process of an individual with cervical medullar injury is significant because the stimuli modulation is at the same level as the one done by the physiotherapists, it was understood from the three subject’s reports that the Physical Education professional contributes to one’s motor gain alongside the medullar injury. We consider that the insertion of a physical education professional is effective in this individual’s multidisciplinary team. Therefore, we conclude that neuroplasticity is a study area and of Physical Education professionals’ interest, however more studies in the area are necessary to know and to practice this process in our application on individuals with medullar injury.